Redesain Map Rekam Medis di Puskesmas Medan Johor - Esraida Simanjuntak; Valentina Valentina; Azizah Putri Syafa Harahap (HB PRESS, 2022)
A folder is a cover of thick paper used to store medical record sheets, which functions to unite all the sheets of a patient so that they become one complete history, protect the medical record files inside so that they are not easily damaged, torn and folded as well as facilitate storage, search and transfer medical record file. The purpose of this study was to redesign the medical record folder in terms of anatomical, physical and content aspects, as well as form boundaries between the forms of family members (father, mother and child) at the Medan Johor Public Health Center. The methods used in this research were observation and interviews. The subjects of this study were medical record folders, and the informants in this study were medical records officers at the Medan Johor Public Health Center. The results showed that in the anatomical aspect in the Heading section it was found that the medical record folder of the Medan Johor Public Health Center only contained the name of the public health center and the logo. In the physical aspect, it was found that the medical record folder of the Medan Johor Public Health Center had a non-durable quality, namely cardboard. In terms of content, it was found that the medical record folder at the Medan Johor Public Health Center did not contain the words CONFIDENTIAL, the allergy column, and the year of the last visit.